2015
DOI: 10.1007/s40089-015-0154-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermal gravity analysis for the study of stability of graphene oxide–glycine nanocomposites

Abstract: In this work, we synthesized graphene oxideglycine (GO-G) nanocomposite. To produce this nanocomposite with GO surface, glycine with known concentration was added to GO suspension in ethanol solvent. Nanocomposites provided were characterized by scanning electron microscope (SEM) and Fourier transform infrared (FT-IR) spectroscopy, respectively. Thermogravimetric analysis (TGA) was employed to investigate the thermal stability of these nanocomposites. Results of characterization by SEM and FT-IR showed that na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 15 publications
2
24
0
Order By: Relevance
“…41 Different studies have shown the adsorption ability of dyes on a large variety of non-conventional low-cost adsorbents, such as agricultural and industrial waste. [41][42][43][44][45][46][47][48][49][50][51][52][53] Nonetheless, in very few cases, for non-conventional adsorbents and low-cost adsorbents, is the adsorption capacity higher than for activated carbons and these adsorbents showed mixed results. So, to develop more efficient adsorbents with a higher capacity for regeneration, the study of nanotubes is an ongoing process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 Different studies have shown the adsorption ability of dyes on a large variety of non-conventional low-cost adsorbents, such as agricultural and industrial waste. [41][42][43][44][45][46][47][48][49][50][51][52][53] Nonetheless, in very few cases, for non-conventional adsorbents and low-cost adsorbents, is the adsorption capacity higher than for activated carbons and these adsorbents showed mixed results. So, to develop more efficient adsorbents with a higher capacity for regeneration, the study of nanotubes is an ongoing process.…”
Section: Introductionmentioning
confidence: 99%
“…So, to develop more efficient adsorbents with a higher capacity for regeneration, the study of nanotubes is an ongoing process. One carbon allotrope is carbon nanotubes (CNTs, 1D) consisting of sp 2 -hybridized carbons, 54 graphene (2D), 53,54 as well as graphite (3D). 55 Since CNTs were discovered in 1991 by Iijima, 56 a variety of them have become available, such as single, double, few, and multi-walled carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…Since 2004, in experimental and theoretical research, graphene has drawn much attention because of its special properties, including its thermal, unique electronic, and physical properties, and it was isolated experimentally . Among the carbon materials, graphene is a single layer sheet that is composed of two‐dimensional hexagonally arrayed sp‐hybridized carbon atoms, and its strength is greater than that of diamond . Also, graphene oxide (GO) is similar to graphene except that GO has the oxygen‐containing functional groups .…”
Section: Introductionmentioning
confidence: 99%
“…10 Among the carbon materials, graphene is a single layer sheet that is composed of two-dimensional hexagonally arrayed sp 2 -hybridized carbon atoms, and its strength is greater than that of diamond. 11,12 Also, graphene oxide (GO) is similar to graphene except that GO has the oxygen-containing functional groups. 13 Graphene and GO are adequate for preparing advanced materials as nanocomposites and nanodevices.…”
Section: Introductionmentioning
confidence: 99%
“…Graphene is the thinnest known material, i.e., a sheet of carbon atoms could be arranged in hexagonal cells of only a single atom thick and yet be stronger than diamond [3]. Since it was experimentally isolated in 2004, it has been the object of intense theoretical and experimental research [4,5].…”
Section: Introductionmentioning
confidence: 99%